Values of Arctic Protected Areas: A Summary - Pagnan, Jeanne; Legare, Gregg (Published by Parks Canada on behalf of the Conservation of Flora and Fauna Program of the Arctic Council. This publication was made possible by funding assistance from Environment Canada., 2002)
Contributors: Heikki Eeronheimo, Ellen Fritts, Jan-Petter Huberth Hansen, Mette-Astrid Jessen, Jim Johnston, Bas Oosenbrug, Aevar Petersen, Vladimir Pischelev, Gunn-Britt Retter, Tamara Semenova, Sune Sohlberg, Page Spence Photo credits: Arendal and the Norwegian Mapping Authorities Environmental Unit, Roger Robinson, EarthLore Communications, Contributing Authors Design and Layout: EarthLore Communications, Ottawa, Canada Available from: CAFF International Secretariat, Borgir 5th Floor Nordurslod 600 Akureyri, Iceland Tel: +354 462 3350 Fax: +354 462 3390, E-mail: CAFF@CAFF.IS WWW.CAFF.IS Descriptions of the natural physical, natural ecological, economic, cultural, subsistence use, educations, landscape, societal, scientific and recreational values of Arctic protected areas.